Duncan McArthur papers - McArthur, Duncan, 1772-1839.
Correspondence, land survey notes, plats, tax returns, and other documents on land holdings in and near the Scioto Valley in Ohio; account books; orderly book of the U.S. Army 19th Infantry Regiment during the War of 1812; and printed matter. With the correspondence are army returns, reports, and general orders for the years 1814-1815, while McArthur was in command of the U.S. Army Dept. of the Northwest; other papers relate to the period of his congressional service. Includes papers of McArthur's daughters.
Library of Congress Rare Book and Special Collections Division.
Ohio governor and legislator, military officer, and U.S. representative from Ohio.
Collection material in English.
Finding aid available in the Library of Congress Manuscript Reading Room and at
Keywords: United States. -- Army. -- Department of the Northwest; United States. -- Army. -- Infantry Regiment, 19th (1812-1815); Land tenure -- Ohio; Ohio -- Politics and government; Scioto River Valley (Ohio) -- History; United States -- History -- War of 1812.; United States -- Politics and government -- 1817-1825.; McArthur family; Army officers; Governors -- Ohio; Legislators -- Ohio; Representatives, U.S. Congress -- Ohio